Jurisdictional Power and Legal Regimes in Language Preservation - Sabzali Musa Kahn; Iskandarsyah Siregar (VRISPRAAK : International Journal of Law, 2026)
This linguistic study examines legal rules on language preservation using legal theory, critical discourse analysis, and corpus-based methods. We use a 2021–2026 legal-linguistic corpus of 126 public documents. Qualitative, quantitative, and triangulated analyses explore how legal discourse shapes preservation policies. The research finds that the wording and context of policy statements greatly influence their effectiveness. Heritage establishment, when supported by obligatory language and institutional enforcement, shows the strongest correlation with preservation (r = 0.73, p < .01). By contrast, references to freedoms in the Bracketing Frame Section are mostly declarative. They state rights rather than implement them, and those rights are only partly realised in practice. The Resource Frame introduces economic considerations and reduces the likelihood of Minicommodification, which is symbolic policy change. Qualitative analysis shows that legal texts function as performative discursive systems. In these systems, language and structure are crucial. Triangulated global data indicate that regions with enforceable legal frameworks demonstrate stronger language vitality, especially in educational settings. This contrasts with areas experiencing domain loss. However, digital linguistic equality remains uneven. Some processes are inaccessible to those outside relevant institutions. The study concludes that law serves as a linguistic agent. Effective preservation depends on enforceable, discourse-sensitive legal frameworks that adapt to technology.